Potential of Fosbio® for building phosphorus and boron levels in a production system (Research, Society and Development, 2024)
This study aimed to evaluate the effectiveness of applying Fosbio® (Rocafeed) in the phosphating of production systems involving the cultivation of corn and oats, analyzing the levels of phosphorus and boron in the soil at depths of 0 to 20 cm and 20 to 40 cm. The research was conducted at Fazenda Santa Cruz, located on Rodovia MG 453/Km 13, in the City of Paraguaçu-MG, during the year 2023. The chemical parameters were subject to analysis, and based on the results obtained, the adequate amount of Fosbio® to be applied to the area, distributing it before planting commercial crops. The treatments consisted of: for corn, T1 - Control, T2 - 516 kg/ha-1 of Fosbio® and T3 – 1.235 kg/ha-1 of Fosbio®; for oats, T1 - Control, T2 - 500 kg/ha-1 of Fosbio® and T3 – 1.000 kg/ha-1 of Fosbio®. The experiment was implemented using the Randomized Block Design (RBD) with 5 replications per treatment, and the parameters evaluated (corn and oats) included productivity, phosphorus (P) and boron (B) content in the soil before planting and after planting. harvest, in layers from 0 to 20 cm and 20 to 40 cm. The means obtained were compared using the Scott-Knott test with 5% probability, using the SISVAR® software. The results indicated that Fosbio® demonstrated effectiveness in increasing phosphorus and boron levels in the soil, standing out as a promising source for phosphating in improving soil fertility in production systems.